Identificación de áreas estratégicas para la localización de vivienda campestre en Ibague (2019)
The city of Ibague, due to its strategic location and its proximity to major cities such as Bogotá, Medellín and Cali, has undergone a considerable expansion by the constructive development in the housing sector, this provoked a population increase of 350,000 inhabitants in The year 1990 to 580,000 today. This situation coupled with a lack of planning has generated a series of problems such as lack of equipment, roads, public services, among other circumstances that are a constant at the national level. One of the main situations that afflict this city due to the lack of planning is the development of rural housing.